Quality of aged shoulder from lambs fed with different oldman saltbush hay levels (Atriplex nummularia) - Alvarenga, Tharcilla Isabella Rodrigues Costa; Borba, Hirasilva; Moreno, Greicy Mitzi Bezerra; Araújo, Gherman Garcia Leal De; Mello, Juliana Lolli Malagoli De; Dourado, Rita De Cássia; Barbosa, José Carlos; Souza, Pedro Alves De (Universidade Federal de Santa Maria, 2014)
This study assessed the effects of different levels of oldman saltbush hay and ageing time on the physical characteristics of Santa Inês lamb meat. Sixty shoulders from 32 male lambs fed with 30, 40, 50 or 60% oldman saltbush hay for 60 days were vacuum-packaged and stored in a refrigerator at 0 ± 1°C for 0, 7 or 14 days of ageing. The shear force, cooking loss and water holding capacity were 3.06kgf cm-2, 37.28% and 76.71%, respectively, and there were no significant changed by studied factors (P>0.05)

Objetivou-se com este trabalho avaliar o efeito da inclusão de diferentes níveis de feno de erva-sal e tempo de maturação sobre as características físicas da carne de cordeiros Santa Inês. Sessenta paletas apartir de 32 cordeiros machos, alimentados com 30, 40, 50 e 60% de feno de erva-sal por 60 dias foram embaladas a vácuo e mantidas sob refrigeração a 0±1oC por 0, 7 e 14 dias de maturação. A força de cisalhamento, perda por cocção e capacidade de retenção de água não foram influenciados (P>0,05) pelos fatores estudados, apresentando valores médios de 3,06kgf cm-2, 37,28% e 76,71%, respectivamente
Qualidade da paleta maturada de cordeiros alimentados com diferentes níveis de feno de erva-sal (Atriplex nummularia)
Keywords: perda por cocção; maciez; maturação; ovinos; cooking loss; tenderness; ageing; sheep